Laparoscopic subtotal cholecystectomy (LSC): a comparison of “Fenestrating” versus “Reconstituting” types - Ahmed, Nisar; Khan, Mohammad Imran (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the outcomes of Fenestrating and Reconstituting subtypes of laparoscopic subtotal cholecystectomy in technically difficult cases. Method: The retrospective study was conducted at the Department of Surgery, Khyber Teaching Hospital, Peshawar, Pakistan, from August 1, 2023, to July 31, 2024, and comprised data of patients who underwent Fenestrating or Reconstituting laparoscopic subtotal cholecystectomy between January 1, 2014, and December 31, 2023, for gallstone disease. Postoperative length of hospital stay, frequency of bile leak, bile collections, requirement of endoscopic retrograde cholangiopancreatography and reoperations were the parameters noted and compared. Data was analysed using IBM® SPSS® Statistics 26.0. Results: Of 1,579 patients, 78(4.9%) had undergone laparoscopic subtotal cholecystectomy. Of them, 6(7.7%) cases were i excluded due to incomplete records, and the final sample comprised 72(92.3%) patients; 44(61.2%) females and 28(38.8%) males with mean age 56.91±16.28 years. Overall, 43(59.7%) patients were in the Fenestrating group and 29(40.3%) in the Reconstituting group. Mean postoperative hospital stay was significantly different between the groups (p<0.05), while the frequency of bile leak, bile collection, requirement of endoscopic retrograde cholangiopancreatography and the rate of reoperations were not significantly different between the groups (p>0.05). Conclusion: Compared to the Fenestrating type, the Reconstituting type of laparoscopic subtotal cholecystectomy resulted in reduced postoperative hospital stay. Key Words: Laparoscopic, Subtotal cholecystectomy, Fenestrating, Reconstituting.